Vibration based predictive maintenance: common rotating machinery faults and their signatures - Mansor, Siti F.; Abdul Muthalif, Asan Gani; Zaman, Nurul 'I (IIUM Press, 2011)
Predictive maintenance method makes use of human senses or other sensitive instruments like audio gauge, amplitude meter, pressure/ temperature strain gauge, vibration analyzer, etc. In this maintenance, equipment conditions are measured continuously. It helps determine the condition of in-service equipment in order to predict when maintenance should be performed. Operating cost can be reduced caused by improved efficiency and productivity, and greater utilization of production time. The predictive maintenance philosophy of using vibration information to lower operating costs and increase machinery availability is gaining acceptance throughout the industry. Vibration is one of the methods used to determine machinery condition. It is the most effective method in predictive maintenance.